2008
DOI: 10.1523/jneurosci.1196-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

The Processing of Color, Motion, and Stimulus Timing Are Anatomically Segregated in the Bumblebee Brain

Abstract: Animals use vision to perform such diverse behaviors as finding food, interacting socially with other animals, choosing a mate, and avoiding predators. These behaviors are complex and the visual system must process color, motion, and pattern cues efficiently so that animals can respond to relevant stimuli. The visual system achieves this by dividing visual information into separate pathways, but to what extent are these parallel streams separated in the brain? To answer this question, we recorded intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
164
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(168 citation statements)
references
References 76 publications
4
164
0
Order By: Relevance
“…1). They peak at 556, 436, and 344 nm, respectively (Menzel and Blakers 1976;Peitsch et al 1992). The green LED was capable of selectively stimulating the green channel because the blue photoreceptor channel has virtually no sensitivity above 500 nm.…”
Section: Discussionmentioning
confidence: 99%
“…1). They peak at 556, 436, and 344 nm, respectively (Menzel and Blakers 1976;Peitsch et al 1992). The green LED was capable of selectively stimulating the green channel because the blue photoreceptor channel has virtually no sensitivity above 500 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Recordings with each visual stimulus as well as control recordings were replicated three times per bee. The minimum interstimulus interval was 1 min, thus avoiding potential adaptation to light stimuli (Paulk et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Knowledge of AOTu function in bees was scarce, and the few previous recordings obtained from isolated neurons pointed to a possible involvement of the AOTu in the processing of chromatic information (Paulk et al, 2008(Paulk et al, , 2009). Here we provide the first functional data on AOTu neural populations.…”
Section: Aotu Function In a Physiological And Behavioral Contextmentioning
confidence: 99%
“…LT11, a pair of bilateral hemivisual-field VPNs, have been shown to play a role in spectrum-specific phototaxis (Otsuna et al, 2014). In bees, electrophysiological studies have demonstrated that neurons innervating the deep lobula strata (Lo5-6) are color sensitive and in general have a larger receptive field than the corresponding medulla neurons (Hertel, 1980;Paulk et al, 2008). Given that the central brain targets of lobula output neurons (VPN) lack retinotopic organization, the lobula seems likely to transform images into feature-based information, such as associating color and motion visual attributes with objects.…”
Section: Introductionmentioning
confidence: 99%